The comparative advantage and relative impact of Asian emerging economies in low carbon energy technological systems - Chan, Y.W.; Zi, X.K.; Mohamad, Z.F.; Arif Azizan, S. (2015)
This paper highlights the specificities of the patterns of low carbon energy technological innovations in selected Asian emerging economies. China and the members of ASEAN-4 (Thailand, Malaysia, Indonesia and the Philippines) are included in this analysis for their identical structure of developing economies. We outline a synthetic framework to cluster the technologies with similar characteristics and analyse the changes of these characteristics over time to elucidate the scope of sectoral composition and specialisation of the selected economies, in order to understand the relative impact of science-based low carbon energy technologies on the niches of technological excellence. The findings show that China was keen to pursue its diversification strategy and develop its capability in low carbon energy technologies since the tum of the millennium. However, China has been gradually losing its momentum in more traditional areas like biomass, hydroelectric power, natural gas and fossil fuels. The ASEAN-4 economies, on the other hand, are showing interest in building a number of niches of technological excellence. This highlights a contrasting relative technological advantage between large and smaller economies. Our findings also indicate that many of the low carbon technologies in selected economies have yet to attain strong scientific grounding for development. The findings of this paper are expected to provide some insights into low carbon energy technological development of emerging economies, and be useful for other developing economies to establish their strategic moves for energy industrial development.